Self-Management of Patient Body Position, Pose, and Motion Using Wide-Field, Real-Time Optical Measurement Feedback: Results of a Volunteer Study - Parkhurst, James M.; Price, Gareth J.; Sharrock, Phil J.; Jackson, Andrew S.N.; Stratford, Julie; Moore, Christopher J. (International journal of radiation oncology, biology, physics, 2013)
We present the results of a clinical feasibility study, performed in 10 healthy volunteers undergoing a simulated treatment over 3 sessions, to investigate the use of a wide-field visual feedback technique intended to help patients control their pose while reducing motion during radiation therapy treatment. An optical surface sensor is used to capture wide-area measurements of a subject's body surface with visualizations of these data displayed back to them in real time. In this study we hypothesize that this active feedback mechanism will enable patients to control their motion and help them maintain their setup pose and position. A capability hierarchy of 3 different level-of-detail abstractions of the measured surface data is systematically compared. Use of the device enabled volunteers to increase their conformance to a reference surface, as measured by decreased variability across their body surfaces. The use of visual feedback also enabled volunteers to reduce their respiratory motion amplitude to 1.7 ± 0.6 mm compared with 2.7 ± 1.4 mm without visual feedback. The use of live feedback of their optically measured body surfaces enabled a set of volunteers to better manage their pose and motion when compared with free breathing. The method is suitable to be taken forward to patient studies.